Designing English Speaking Materials Using Task Based Language Teaching (TBLT) For Islamic Economics Students - Linda Septiyana (Institut Agama Islam Negeri Palopo, 2019)
This research aimed to 1) describe the steps of designing English speaking materials using Task-Based Language Teaching (TBLT) for Islamic Economics Students of IAIN Metro 2) determine the students’ responses toward English Speaking Materials using Task-Based Language Teaching (TBLT). The type of this research was Research and Development (R&D). This research was conducted within 5 months. The subjects were students of the Islamic Economics Department of IAIN Metro. The results showed that 1) the steps in designing English speaking materials using Task-Based Language Teaching (TBLT) are potency and problem, data collection, product design, design validation, design revision, product testing, product revision. Product testing was used to determine the students’ responses toward the product. and 2) The results of students' responses analysis towards English speaking materials using Task-Based Language Teaching (TBLT) which distributed to 24 Islamic Economics students were very good. It can be seen from the the average score after being converted into quantitative data that was 3.46. Therefore, English speaking materials using Task-Based Language Teaching (TBLT) are considered reasonable to use.